2009
DOI: 10.1093/eurheartj/ehp489
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus-related activation of the cardiomyocyte mitochondrial apoptotic pathway in patients with acute myocarditis

Abstract: Our findings evidence an EV-related activation of the cardiomyocyte mitochondrial apoptotic pathway in patients with acute myocarditis. Moreover, our results indicate that this EV-induced pro-apoptotic mechanism could be partly related to an up-regulation of Bax expression, and suggest that inhibition of this cell death process may constitute the basis for novel therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…However, experimental 27,28 and clinical studies have shown that virus-induced cardiomyocyte apoptosis also has a deleterious effect on LV function, leading to severe heart failure and, in severe cases, death. [29][30][31] In the present study, EMCV-induced cardiac myocyte apoptosis and caspase 3 cleavage were attenuated in αMHC-MDA5 transgenic mice compared with infected LM controls. The decreased prevalence of apoptosis and caspase 3 cleavage in αMHC-MDA5 mice can be explained, at least in part, by the significantly lower viral loads in the hearts of these mice.…”
Section: Discussionsupporting
confidence: 51%
“…However, experimental 27,28 and clinical studies have shown that virus-induced cardiomyocyte apoptosis also has a deleterious effect on LV function, leading to severe heart failure and, in severe cases, death. [29][30][31] In the present study, EMCV-induced cardiac myocyte apoptosis and caspase 3 cleavage were attenuated in αMHC-MDA5 transgenic mice compared with infected LM controls. The decreased prevalence of apoptosis and caspase 3 cleavage in αMHC-MDA5 mice can be explained, at least in part, by the significantly lower viral loads in the hearts of these mice.…”
Section: Discussionsupporting
confidence: 51%
“…For each patient, a mean number of 2.1 (SD ϭ 1.3; range, 1 to 7) large heart tissue samples were fixed, within 2 h of heart transplantation, in 10% neutral buffered formalin and paraffin embedded for classical histopathological analyses (13). All of these 67 heart tissue samples demonstrated histopathological findings compatible with DCM (14).…”
Section: Patientsmentioning
confidence: 99%
“…7,9,26 Reports already documented that cardiomyocytes apoptosis occurs and contributes to development and severity of CVB3-induced AVMC. 37,38 About the link between ER stress/CHOP signaling and apoptosis, it suggests that ER stress and its downstream activator CHOP may also be emerged in AVMC development induced by CVB3. Our observation truly confirmed this hypothesis by identifying CHOP activation accompanied with increased cardiomyocytes apoptosis in AVMC hearts.…”
Section: Discussionmentioning
confidence: 99%